The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/jcc.25740
|View full text |Cite
|
Sign up to set email alerts
|

Benson group additivity values of phosphines and phosphine oxides: Fast and accurate computational thermochemistry of organophosphorus species

Abstract: Composite quantum chemical methods W1X‐1 and CBS‐QB3 are used to calculate the gas phase standard enthalpy of formation, entropy, and heat capacity of 38 phosphines and phosphine oxides for which reliable experimental thermochemical information is limited or simply nonexistent. For alkyl phosphines and phosphine oxides, the W1X‐1, and CBS‐QB3 results are mutually consistent and in excellent agreement with available G3X values and empirical data. In the case of aryl‐substituted species, different computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 82 publications
(195 reference statements)
0
8
1
Order By: Relevance
“…Consequently, systematic differences between W1X-1 and CBS-QB3 can be attributed to inadequate treatment of electron correlation effects in the latter that become more prominent with increasing molecular size. This is in stark contrast to our previous study on phosphines and phosphine oxides, 31 in which case W1X-1 and CBS-QB3 showed much more uniform performance, albeit for a more limited set of compounds with less variety in the employed substituents. W1X-1 enthalpies are, therefore, considered superior to CBS-QB3 results and used exclusively in the remaining parts of the analysis and discussion.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Consequently, systematic differences between W1X-1 and CBS-QB3 can be attributed to inadequate treatment of electron correlation effects in the latter that become more prominent with increasing molecular size. This is in stark contrast to our previous study on phosphines and phosphine oxides, 31 in which case W1X-1 and CBS-QB3 showed much more uniform performance, albeit for a more limited set of compounds with less variety in the employed substituents. W1X-1 enthalpies are, therefore, considered superior to CBS-QB3 results and used exclusively in the remaining parts of the analysis and discussion.…”
Section: Resultscontrasting
confidence: 99%
“…While this convention has been adopted by some authors, including Benson in his later works, 15 we chose to report group pair contributions following the practice adopted in our previous work. 31 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In some instances, such as with organosilicon compounds, 31 inconsistencies in the reference data have completely prevented the determination of an internally consistent set of group contributions by experimental means. As shown by us 32,33 and by others, 103107 a simple fix to the problem is offered by theoretical approaches and high-level composite methods in particular. In the following, we follow this avenue and determine Benson group contributions for boron using the highlevel W1X-1 data in Table 1.…”
Section: Comparison Of Calculated Gas Phase Standard Enthalpies Of Fo...mentioning
confidence: 99%